Effect of polysaccharide concentration and charge density on acid-induced soy protein isolate-polysaccharide gels using HCl. (July 2017) - Wee, M.S.M.; Yusoff, R.; Lin, L.; Xu, Y.Y
Graphical abstract: Highlights: Soy protein isolate-polysaccharide gels formed by acidification with simulated gastric fluid. Increasing hardness and G with polysaccharide concentration and charge density. Improved water holding capacity and freeze-thaw stability at 1.0% w/w polysaccharide. Abstract: Mixed biopolymer gels of soy protein isolate with κ-carrageenan, λ-carrageenan and alginate were produced via acidification with simulated gastric fluid (HCl) at pH 1.2. The gels could be formed instantaneously via dripping into the acid, or over 24 h via a dialysis membrane. The main factors studied were charge density of the polysaccharide and polysaccharide concentration (0.25 − 1.0% w/w). Their effects on the physical properties of the gel i.e. gel mass formed, protein concentration in supernatant, hardness, storage modulus (G′), water holding capacity (WHC) and microstructure were evaluated. Overall, with higher charge density of the polysaccharide (at pH 1.2) and/or increasing polysaccharide concentration, the gel formed more rapidly and had greater mechanical strength due to a denser network between the biopolymers. As a result, WHC was also increased with improved freeze-thaw stability as observed under confocal microscopy.